2022
DOI: 10.7554/elife.76649
|View full text |Cite
|
Sign up to set email alerts
|

Tension-driven multi-scale self-organisation in human iPSC-derived muscle fibers

Abstract: Human muscle is a hierarchically organised tissue with its contractile cells called myofibers packed into large myofiber bundles. Each myofiber contains periodic myofibrils built by hundreds of contractile sarcomeres that generate large mechanical forces. To better understand the mechanisms that coordinate human muscle morphogenesis from tissue to molecular scales, we adopted a simple in vitro system using induced pluripotent stem cell-derived human myogenic precursors. When grown on an unrestricted two-dimens… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 81 publications
0
12
0
Order By: Relevance
“…Following mLCN film preparation, we seeded C2C12 myoblasts at a relatively low density (5000 cells/cm 2 ) on sterilized mLCNs as well as gelatin-coated glass coverslips for an additional isotropic, stiff control used in myoblast culture ( 24 ). Consistent with previous reports, we observed that C2C12s adhered to neat mLCNs, presumably due to nonspecific protein adsorption from the growth medium ( 13 , 16 , 25 ).…”
Section: Resultsmentioning
confidence: 99%
“…Following mLCN film preparation, we seeded C2C12 myoblasts at a relatively low density (5000 cells/cm 2 ) on sterilized mLCNs as well as gelatin-coated glass coverslips for an additional isotropic, stiff control used in myoblast culture ( 24 ). Consistent with previous reports, we observed that C2C12s adhered to neat mLCNs, presumably due to nonspecific protein adsorption from the growth medium ( 13 , 16 , 25 ).…”
Section: Resultsmentioning
confidence: 99%
“…Instead, they arise after fusion and are strongly correlated with myofibril assembly, suggesting that positioning of myonuclei is regulated by myofibrillogenesis. Previous studies have proposed a link between myofibril formation and myonuclei location 67,79,80 , but in vitro studies have found that forming myofibrils drive nuclei to the myofiber periphery 67 . However, in myofibers regenerated in vivo after a catastrophic injury, the initial myonuclei remain in centralized chains; we hypothesize that the rapidity of myocyte-myocyte fusion, nearly synchronous formation of myofibrils, and the enclosing BM traps and positions myonuclei into centralized chains.…”
Section: Discussionmentioning
confidence: 99%
“…Each of these models is supported by some experimental observations but may be incompatible with others ( Chopra et al, 2018 ; Fenix et al, 2018 ; Rui et al, 2010 ). In addition, mechanical tension generated by attachment of myofibers to tendon, myofiber bundling, and formation of mini-sarcomeres is also found to promote sarcomere assembly in both fly and mammalian muscle cells ( Chopra et al, 2018 ; Loison et al, 2018 ; Luis and Schnorrer, 2021 ; Mao et al, 2022 ; Weitkunat et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%